2021
DOI: 10.1016/j.ijcard.2021.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Smartwatch Electrocardiogram and Artificial Intelligence for Assessing Cardiac-Rhythm Safety of Drug Therapy in the COVID-19 Pandemic. The QT-logs study

Abstract: Background: QTc interval monitoring, for the prevention of drug-induced arrhythmias is necessary, especially in the context of coronavirus disease 2019 . For the provision of widespread use, surrogates for 12-lead ECG QTc assessment may be useful. This prospective observational study compared QTc duration assessed by artificial intelligence (AI-QTc) (Cardiologs®, Paris, France) on smartwatch single-lead electrocardiograms (SW-ECGs) with those measured on 12-lead ECGs, in patients with early stage COVID-19 trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 34 publications
1
28
0
Order By: Relevance
“…Post-processing and data analysis relies on raw data, but, sometimes, accessing only the post-processed data may be enough. Such post-processing can be performed externally, as showcased, for example, in [ 99 , 107 ], wherein the obtained location data and ECG data were processed by an external server and a mobile phone application, respectively. Once the post-processed data is available on a Cloud server, it could be accessible through the Cloud or Ethernet/IP protocols.…”
Section: Wearable Sensors For Measuring Loneliness And/or Social Isol...mentioning
confidence: 99%
“…Post-processing and data analysis relies on raw data, but, sometimes, accessing only the post-processed data may be enough. Such post-processing can be performed externally, as showcased, for example, in [ 99 , 107 ], wherein the obtained location data and ECG data were processed by an external server and a mobile phone application, respectively. Once the post-processed data is available on a Cloud server, it could be accessible through the Cloud or Ethernet/IP protocols.…”
Section: Wearable Sensors For Measuring Loneliness And/or Social Isol...mentioning
confidence: 99%
“…White [33] showed that the concentrations needed to inhibit the hERG channel responsible for QT prolongation were 4 to 14 times higher than the concentrations observed in plasma at usual doses. In our center, we developed a smartwatch electrocardiogram and artificial intelligence for assessing the cardiac rhythm safety of HCQ+AZ and did not find any QTc prolongation [35]. In the literature, ambulatory and not critically ill patients with COVID-19 treated with hydroxychloroquine, azithromycin and/or antiretrovirals develop a significant, but not relevant, QT interval prolongation [36].…”
Section: Discussionmentioning
confidence: 93%
“…Through logical analysis, adjustment, and summary of different data mining models, Egevad et al finally established a new data mining system, which can realize delayed capture and real-time feedback of tourism engineering management data [ 11 ]. Scholars from Safarnejad L and other universities put forward a new data mining model establishment method based on the multirelationship recommendation algorithm according to the multifactor relationship theory in philology, analyzed the correlation of different modules in the traditional data mining model, and established a double factor analysis model [ 12 ]. Verganti et al comprehensively evaluated the employee management data mining model of a tourism project from the aspects of the selection of the structure form of the tourism management storage database, the classification of the content, and the storage capacity of the database and realized the simulation of the working process of the model database by capturing different types of data [ 13 ].…”
Section: Related Workmentioning
confidence: 99%